An exercise path to preventing Alzheimer's disease: An Editorial Highlight on 'Exercise and BDNF reduce Ab production by enhancing α–secretase processing of APP'. Issue 2 (18th May 2017) - Coulson, Elizabeth J.; Bartlett, Perry F.
Abstract : Read the highlighted article 'Exercise and BDNF reduce Aβ production by enhancing α-secretase processing of APP' on page 286 . Abstract : This Editorial highlights a study by Nigam and coworkers in the current issue of the Journal of Neurochemistry, in which the authors provide new evidence about how an increase in BDNF levels following exercise can reduce the production of toxic amyloid beta (Aβ) by enhancing α‐secretase processing of amyloid precursor protein (APP). Read the highlighted article 'Exercise and BDNF reduce Aβ production by enhancing α-secretase processing of APP' on page 286 .